Ceremonial entries in early modern Europe : the iconography of power - Mulryne, J. R.; Mulryne, J. R.; Aliverti, Maria Ines; Aliverti, Maria Ines; Testaverde, Anna Maria; Testaverde, Anna Maria (European festival studies: 1450-1700, 2015)
"The fourteen essays that comprise this volume concentrate on festival iconography, the visual and written languages, including ephemeral and permanent structures, costume, dramatic performance, inscriptions and published festival books that 'voiced' the social, political and cultural messages incorporated in processional entries in the countries of Early Modern Europe. The volume also includes a transcript of the newly-discovered Register of Lionardo di Zanobi Bartholini, a Florentine merchant, which sets out in detail the expenses for each worker for the possesso (or Entry) of Pope Leo X to Rome in April 1513"--